GA-based dynamic survivable routing in WDM optical networks with shared backup paths - Le, Vinh Trong (VNU Journal of Science: Mathematics - Physics; Vol 23 No 2, 2007)
Abstract. This paper considers the problem of dynamic survivable routing in WDM networks with single link íailure model. This work mainly concems in how to dynamically đetermine a protection cycle (i.e., two link-disjoint paths between a node pair) to establish a dependable lightpath with backup paths sharing. The problem is identified as NP-complcte, thus a heuristic for fmding near optimal solution with reasonable computation timc is usually preferred. Inspired from the principle of genetic algorithms (GA), a GA-based survivable routing algorithm for the problcm with a new íìtness íunction, which allows us to improve blocking períormance, will be proposed. Extensive simulation results upon the ns-2 network simulator and two typical netvvork topologics show that our algorithm can achieve a signiíìcantly lower blocking probability than conventional algorithms.